Pemahaman Konsep Pada Materi Reaksi Redoks dengan Four-Tier Test - Rahmiati Rahmiati; Ratna Kartika Irawati; Trining Puji Astutik (Al Kawnu : Science and Local Wisdom Journal, 2022)
This study aims to determine the understanding of the redox reaction material concept of each subconcept in class X students of MAN 3 Hulu Sungai Selatan. The type of research used is descriptive statistics with a quantitative approach. The population of this study was students of class X MAN 3 Hulu Sungai Selatan with samples of class X MIA 1 and 2 totaling 63 people. Sampling technique used is Purposive Sampling. Data collection techniques were carried out using a four-tier diagnostic test. The results showed that the understanding of the concept of redox material with an average of 31.25% with moderate criteria. Understand the concept of redox reactions based on the binding and release of oxygen by 42.06%, redox reactions based on the attachment and loss of electrons by 26.98%, redox reactions based on increasing and decreasing oxidation numbers by 25.40%, determining the oxidation number of 58, 73%, oxidation-reduction reactions of 26.98%, oxidizing and reducing agents of 24.34%, and the application of redox reactions of 14.29%. Understanding the biggest concept is in the sub-concept of determining the oxidation number.